Comparison of the Effectiveness of Group Therapies “Emotional Freedom Techniques (EFT), Adolescent-Centered Mindfulness Therapy (ACMT) and Dialectical Behavior Therapy (DBT)” on the Emotion Regulation in Adolescents with Disruptive Mood Dysregulation Disorder (DMDD) - Ghaheri, Pezhman; Bahramipour Isfahani, Mansoureh; Torkan, Hajar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Background: The present study was conducted with the aim of comparison of the effectiveness of group therapies “emotional freedom techniques (EFT), adolescent-centered mindfulness therapy (ACMT) and dialectical behavior therapy (DBT)” on the emotion regulation in adolescents with disruptive mood dysregulation disorder (DMDD).Methods: The research was semi-experimental in three stages: pre-test, post-test and two-month follow-up with the control group. The statistical population of all adolescents aged 15 to 18 years had symptoms of DMDD in the high schools of NajafAbad province in the academic years of 2023 and 2024. For this aim, using multi-stage cluster random sampling method, 600 students were screened from among the high schools of the 2nd education district by implementing the DMDD Questionnaire of Laporte et al. were randomly assigned to three experimental groups (20 each) and a control group (20). The people of the experimental groups participated in parallel and simultaneous group therapies of EFT, ACMT and DBT; But for the control group, there was no intervention. The measurement tool was Gratz and Roemer (2004) emotion regulation difficulty questionnaire. To analyze the data, the statistical method of analysis of variance with repeated measures and Bonferroni's post-hoc test was used in SPSS-26 software.Results:  In the intergroup comparison, all three therapy methods were effective in reducing the difficulty in emotions regulating of with symptoms of DMDD in the post-test stage (p